2014
DOI: 10.1371/journal.pone.0115763
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Mitochondrial ATP Synthesis in Dystrophin-Deficient Mdx Skeletal Muscles May Be Caused by Complex I Insufficiency

Abstract: Duchenne Muscular Dystrophy is a chronic, progressive and ultimately fatal skeletal muscle wasting disease characterised by sarcolemmal fragility and intracellular Ca2+ dysregulation secondary to the absence of dystrophin. Mounting literature also suggests that the dysfunction of key energy systems within the muscle may contribute to pathological muscle wasting by reducing ATP availability to Ca2+ regulation and fibre regeneration. No study to date has biochemically quantified and contrasted mitochondrial ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 44 publications
9
116
1
Order By: Relevance
“…Transcriptionally, there is a striking resemblance between mNKO muscle and that of the well-characterized mdx model of DMD. This observation was unexpected, given that the former defect is strictly metabolic and the latter strictly structural, and especially compelling in light of reports that mdx muscle contains less NAD than that of age-matched controls and appears limited in aerobic capacity by complex I (Chalkiadaki et al, 2014; Rybalka et al, 2014). NAD supplementation also counteracts at least one additional laminopathy modeled in zebrafish (Goody et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Transcriptionally, there is a striking resemblance between mNKO muscle and that of the well-characterized mdx model of DMD. This observation was unexpected, given that the former defect is strictly metabolic and the latter strictly structural, and especially compelling in light of reports that mdx muscle contains less NAD than that of age-matched controls and appears limited in aerobic capacity by complex I (Chalkiadaki et al, 2014; Rybalka et al, 2014). NAD supplementation also counteracts at least one additional laminopathy modeled in zebrafish (Goody et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…An increasing number of discoveries have shown that inefficient metabolism, due to mitochondrial dysfunction in muscle and brain tissue, could cause blood pressure elevation and may be associated with the development of hypertension [13, 14]. Our recent studies, using electron microscopy analysis, have shown mitochondrial ultrastructural abnormalities in medullary thick ascending limbs of SS rats, implying mitochondrial function may be different [15].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing body of literature (see Table 1) [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] indicating that dystrophin deficiency causes sarcolemmal fragility and intracellular Ca 2+ dysregulation, which generally leads to mitochondrial dysfunction, a reduction in resting adenosine triphosphate (ATP) levels, an increased production of cell-damaging reactive oxygen species (ROS) and ultimately mitochondrial damage. [38][39][40] The combination of primary dystrophin deficiency and secondary mitochondrial dysfunction and impaired muscle cell regeneration, degeneration and cell death is shown in Figure 2A.…”
Section: Rationale For Idebenone As Treatment Approach For Dmdmentioning
confidence: 99%
“…54 As direct evidence of a mitochondrial role in the pathogenesis of muscular dystrophy, mitochondrial biogenesis has been demonstrated to ameliorate the pathology and improve function in the dystrophin deficient mdx mouse model. Specifically, Selsby and colleagues 56 showed that over-expression of peroxisome-proliferator receptor γ coactivator 1α (PGC-1α), resulted in increased utrophin and slow type I myosin heavy chain fibre expression, as well as elevated mitochondrial protein expression and increased expression of oxidative genes.…”
Section: Rationale For Idebenone As Treatment Approach For Dmdmentioning
confidence: 99%
See 1 more Smart Citation